The secreted FolAsp aspartic protease facilitates the virulence of Fusarium oxysporum f. sp. lycopersici - Wang, Chenyang; Zheng, Yaning; Liu, Zhishan; Qian, Yongpan; Li, Yue; Yang, Limei; Liu, Sihui; Liang, Wenxing; Li, Jingtao (Frontiers in Microbiology, 2023)
Pathogens utilize secretory effectors to manipulate plant defense. Fusarium oxysporum f. sp. lycopersici (Fol) is the causal agent of Fusarium wilt disease in tomato. We previously identified 32 secreted effector condidates by LC-MS analysis. In this study, we functionally identified one of the secreted proteins, FolAsp, which belongs to aspartic proteases (Asp) family. The FolAsp was up-regulated with host root specifically induction. Its N-terminal 1-19 amino acids performed the secretion activity in yeast system which supported its secretion in Fol. Phenotypically, FolAsp was not involved in its growth and conidia production, however, its virulence on tomato was significantly decreased in FolAsp deletion mutants. Further study revealed the FolAsp was localized at apoplast and inhibited INF induced cell death in planta. Meanwhile, FolAsp could inhibit flg22 mediated ROS burst. Furthermore, FolAsp displayed protease activity on host protein, and overexpression of FolAsp in Fol enhanced pathogen virulence. These results considerably extend our understanding of pathogens utilizing secreted protease to inhibit plant defense and promote its virulence, which provide potential applications for tomato improvement against disease as the new drug target.